(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article deals with the peculiarities of the outlook of Chechen, Russian and English people shown in the proverbs which demonstrate national and cultural specificity of Chechen, Russian and English linguistic cultures. The presence of different value attitudes, customs have left a certain imprint on the relations between neighbours in the languages, but in the process of research, we have emphasized that in most cases the qualities of good and bad neighbours are identical. The distinctive signs are certainly highlighted – the close interaction that is observed in Chechen and Russian cultures and the opposite picture in English culture. We have analyzed a total of 60 paremiological units of the studied languages, in which the characteristic features and qualities of the neighbours were determined. Keywords: neighbour, relationship, family, house, role, function. DOI 10.23683/1995-0640-2020-1-72-76